Plant stress tolerance : an integrated omics approach - Mosa, Kareem A.; Ismail, Ahmed; Helmy, Mohamed (Springer, 2017)
Providing a comprehensive overview of cutting-edge research on Omics applications in plant sciences field, "Plant Stress Tolerance" focuses on different approaches towards plant stress tolerance including both biotic stresses and abiotic stresses. This book outlines the challenges facing this area of research, with solid, up-to-date information for graduate students, academic scientists and researchers on using the recent advances of Omics technologies on plant stresses.
Keywords: Plants -- Effect of stress on.; elektronické knihy; electronic books